Matching supply and demand for ecosystem services in the Yellow River Basin, China: A perspective of the water-energy-food nexus. (15th January 2023) - Yin, Dengyu; Yu, Haochen; Shi, Yangyang; Zhao, Mingyue; Zhang, Jian; Li, Xiaoshun
Abstract: Under the combined effects of global climate change and human activities, ecological protection in arid and semi-arid regions is facing severe challenges. There is an urgent need to determine how to reconcile the supply and demand of ecosystem services (ESs) to achieve the rational allocation of resources. Therefore, in this study, taking the Yellow River Basin (YRB) as an example, the three ESs of water yield (WY), carbon sequestration (CS), and food provision (FP) were selected from the perspective of the water-energy-food nexus. The spatiotemporal changes and trade-offs of ESs supply and demand in the YRB were evaluated by InVEST model, the supply-demand index (SDI), and the Pearson correlation method. Furthermore, the ESs matching modes were analyzed by the four-quadrant method. Finally, an integrated scheme and suggestions were proposed. The results demonstrated the following. (1) From 2000 to 2018, the supply of the three ESs exhibited spatial patterns similar to those of resource allocation, but the change trends were different. Additionally, the demand for all ESs increased and displayed a spatial pattern of "high in the southeast and low in the northwest." (2) The SDI values of WY and CS decreased, while the trend of FP was contrary. The SDI value of WY was dominated by deficit, while those of CS and FP were mainly dominated by surplus. The supply and demand of these three ESs presented a significant correlation at the city scale. (3) The study area was divided into three dominant functional zones, four classified protection areas, and three types of hierarchical governance models, and differentiated policy recommendations were offered. This research can serve as a reference and basis for the effective allocation of regional resources and sustainable ecosystem management. Highlights: We evaluated the spatiotemporal characteristics of the ESs supply and demand in multi-stage from the perspective of water-energy-food nexus. There were wide variations in the matching patterns of the ESs supply and demand at different scales. We found that the ESs supply and demand relations were all significantly related only at the city scale. We proposed an integrated scheme of zoning control, classification strategy, and hierarchical governance.